Volunteering and Subjective Well-Being Among Individuals With Disabilities: A Multivariate Model. (April 2019) - Kulik, Liat
The main goal of the study was to evaluate the contribution of volunteering to explaining two indicators of subjective well-being—self-esteem and sense of meaning in life (MIL)—among people with physical disabilities in Israel. The sample included 160 Israeli participants with physical disabilities, of whom 95 had volunteered and 65 had not. The findings revealed that volunteering was both directly and indirectly associated with factors that facilitate the sense of MIL but was not associated with factors that inhibit MIL. Furthermore, volunteering was found to mediate the relationship of economic and family support to self-esteem and to facilitators of MIL. The results point to a sequence of contingencies that facilitate indicators of subjective well-being: when people with disabilities have high levels of economic resources and family support, they are more likely to volunteer; in turn, volunteer activity increases self-esteem and promotes a sense of MIL.